Surface termination effects on the terahertz-range optical responses of two-dimensional MXenes: Density functional theory study - Jhon, Young In; Lee, Ju Han; Jhon, Young Min (Elsevier BV, 2022)
Two-dimensional (2D) transition metal carbides referred to as MXenes show excellent terahertz (THz) shielding performance and stealth effectiveness. Differently from other 2D materials, MXenes inherently have surface functionality and consequently, surface termination engineering has been a powerful means to manipulate their physical properties greatly in a predictable way. Despite MXenes' great potential in THz technology, the surface engineering issue has not been examined to date. For the first time, using density functional theory calculations, this study investigated the THz-range optical responses of the most popular MXene, Ti3C2Tx by systematically varying surface termination species among -O, -OH, -F, -Cl, and -Br. We found that O-terminated MXenes showed the highest THz absorption performance of 180,000 cm- 1. Meanwhile, OH-terminated MXenes exhibited sevento-eight times magnitude smaller THz absorption efficiency and F-terminated MXenes showed significantly deteriorated two-order magnitude smaller performance than that of O-terminated MXene. For recently developed surface halogen alternatives, Cl-terminated MXenes have almost the same but slightly lower terahertz absorption efficiency compared to F-terminated MXenes, while Br-terminated MXenes have remarkably enhanced one-order magnitude greater performance. O, OH, and Br-terminated MXenes belong to a good THz absorbing materials in a descending order of O, Br, and OH. We revealed that the THz absorption capacity is intimately related with metallicity that can be recognized by the exceedingly large refractive index at the ultralow photon energy of 0.001-0.002 eV. This study strongly indicated the promising potential of surface termination engineering for tailoring the THz photonics of MXenes.